O teletrabalho no serviço público à luz dos princípios constitucionais da eficiência administrativa e do bom andamento : uma comparação entre a realidade brasileira e a realidade italiana - Duailibe, Anna Carolina Lima Vieira Jansen (2022)
This research analyzes the teleworking regime in public services as an instrument for applying the constitutional principles of administrative efficiency in Brazil and its good performance in Italy. It is known that teleworking is conceptualized as a type of long distance service provision, accomplished through the use of information and communication technology, especially mobile networks, the internet, and any other forms of telecommunication, making it possible for the worker to exercise their activities without the need of traveling to the physical work environment, and it gained strength in the 1970s, when the world was experiencing the oil crisis, and concerns with displacement and expenses were bigger. In the Brazilian legislation teleworking is provided in article 6 of the Consolidation of Labor Laws (CLT) which has chapter II-A dedicated to the theme in the articles 75-A to 75-F. It is noted that the first contact of the modality in Brazil took place in 1997, through the presentation of the Home Office/Telecommuting Seminar - business and work perspectives for the third millennium, and then, in 1999, with the creation of the Brazilian Society of Telework and Teleactivity (SOBRATT). It is stablished that Italy was a pioneer in the provision of telework within the scope of public administration, through Law nº 191/1998, analyzing its legislation on the subject. The principles of Public Administration provided in the Brazilian Constitution are demonstrated, which are the principles of legality, impersonality, morality, publicity, and efficiency shown in its article 37 and, in more depth, the principle of administrative efficiency and the principle of good performance, which is listed in article 97 of the Italian Constitution, based on a comparative study between the realities of the two countries. It concludes that teleworking is another instrument to make Public Administration efficient for those who use it and for those who assemble it, making it evident that the modality of work, amid positive and negative implications, celebrates the principle of administrative efficiency and good performance in all its aspects.